AI and the Future of Autonomous Decision-Making: Ethical Considerations (Journal of responsible AI & ethics, 2026)
The rapid development of Artificial Intelligence (AI) has led to an increasing reliance on autonomous systems capable of making critical decisions without human intervention. These systems, powered by machine learning algorithms and data-driven processes, are increasingly being used in sectors such as healthcare, transportation, finance, and defense. However, the widespread deployment of AI-driven decision-making raises significant ethical concerns about accountability, transparency, and the potential for bias in algorithmic outputs. This paper explores the ethical implications of autonomous decision-making systems, focusing on the challenges of ensuring fairness, privacy, and human oversight. By examining existing case studies, theoretical frameworks, and empirical research, the paper assesses the risks and benefits of AI in autonomous decision-making and offers recommendations for responsible AI governance. The study concludes that while AI has the potential to enhance decision-making efficiency and accuracy, careful consideration must be given to the ethical risks associated with algorithmic autonomy, particularly regarding its impact on individual rights and societal norms.